Synthesis, Characterization, and Selected Properties of 7‐ and 12‐Ammoniocarba‐closo‐dodecaboranes. Issue 1 (9th November 2012) - Konieczka, Szymon Z.; Himmelspach, Alexander; Hailmann, Michael; Finze, Maik
Abstract: The inner salts 12‐H3 N‐ closo ‐1‐CB11 H11 (H1 ) and 7‐H3 N‐12‐Hal‐ closo ‐1‐CB11 H10 [Hal = F (H3 ), Cl (H4 )] were synthesized by a microwave‐assisted Buchwald–Hartwig amination starting from the corresponding monoiodinated { closo ‐1‐CB11 } clusters and LiN(SiMe3 )2 . H1 was methylated to result in the zwitterion 12‐Me3 N‐ closo ‐1‐CB11 H11 (2 ). All new compounds were characterized by multinuclear NMR spectroscopy, elemental analysis, and mass spectrometry. The crystal structures of H1· Me2 CO and2 were determined. The p K a value of H1 in aqueous solution was estimated by potentiometric titration and by 11 B{ 1 H} NMR spectroscopic studies. The stepwise deprotonation of H1 with n BuLi in [D8 ]THF was studied by multinuclear NMR spectroscopy. In a first step, the amine1 is obtained and then the amide [12‐HN‐ closo ‐1‐CB11 H11 ] 2– and finally the trianion [12‐HN‐ closo ‐1‐CB11 H10 ] 3– or more probably lithiated species thereof are formed. The experimental spectroscopic and structural data, as well as the p K a value of H1 are compared to values derived from DFT and ab initio calculations. Abstract : Carba‐ closo ‐dodecaboron clusters with an ammonio substituent bonded to the 7‐ or 12‐position of the cluster were synthesized by a microwave‐assisted Buchwald–Hartwig cross‐coupling reaction. Selected spectroscopic and chemical properties of 12‐H3 N‐ closo ‐1‐CB11 H11 and 7‐H3 N‐12‐Hal‐ closo ‐1‐CB11 H10 (Hal = F, Cl) are reported and compared to data derived from theoretical calculations.